Factors Influencing the Choice of Toothpaste and Investigation of Those Most Commercialized by Students in Settat, Morocco - Rahim, Abdellatif; El Karfi, Wissal; Katir Masnaoui, Lalla Asmaa; El Amiri, Bouchra; Essamadi, Abdel Khalid (Makara Journal of Health Research, 2022)
Background: This study aimed to determine the factors influencing the choice of toothpaste by students in Settat (Morocco) and investigate the characteristics of those most commercialized in this region. Methods: A close-ended questionnaire was developed and filled out. This was a cross-sectional study of 429 students who agreed to participate. Based on questionnaire data, the 15 most commercialized toothpaste by respondents were purchased, and their packaging was investigated. Results: After analysis using Excel 2019, the results revealed that the major factors influencing the choice of toothpaste are brand 55%, family choice 48%, and media advertisements 40%. Moreover, about 57% of respondents chose toothpaste brands with monofluorophosphate as a therapeutic fluoridated agent, whereas 41% chose those with NaF. In addition, 85% of respondents chose a toothpaste brand that has silica abrasive. Moreover, only 44% chose toothpaste with production and expiration dates. Finally, the total fluoride and total soluble fluoride were lower compared with the quantity of fluoride expected from the packaging. Conclusions: The present study indicated that the respondents selected their toothpaste primarily based on brands, family choices, and media advertisements. Incomplete labeling was encountered in toothpaste used by 58% of the respondents.